Analysis of E-Ticketing Technology for Inspection Performance and Practicality on Asphalt Paving Operations. Issue 8 (August 2022) - Tripathi, Amit; Patel, Dhaivat; Sturgill, Roy; Dadi, Gabriel B.
E-construction is becoming increasingly attractive in the highway construction industry as the industry faces reductions in staffing and resources. Specifically, the addition of e-construction methods can offer a boost in efficiency and safety in resurfacing projects. Electronic ticketing (e-ticketing), paver-mounted thermal profiling, and intelligent compaction were recently incorporated into a study coordinated by the Kentucky Transportation Cabinet, United States, to assess these e-construction technologies on two resurfacing projects. This study aimed to investigate the accuracy of the data collected and the time savings that come with the incorporation of technology in construction. This manuscript focuses explicitly on the performance of e-ticketing, since it showed the most promising results during the study. An analysis of the data shows that e-ticketing offers the same data typically collected from traditional tickets. E-ticketing reduced the amount of time needed to retrieve material tickets and facilitated comparisons of theoretical tonnages to actual tonnages, in the same manner as traditional approaches. Inspectors also reduced their exposure to hazardous jobsite conditions through the use of e-ticketing, while contractors strengthened their operational efficiency. It is crucial that all stakeholders involved in e-ticketing projects practice partnering and collaboration to take advantage of the benefits of this emerging technology. This paper's primary contribution is to document lessons learned and to evaluate the performance of e-ticketing technology in relation to safety, time savings, remote inspections, and accuracy compared with traditional practices on an asphalt paving project.